2014
DOI: 10.1111/ina.12158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with nonspecific building-related symptoms in office employees in Japan: relationships between work environment, Indoor Air Quality, and occupational stress

Abstract: A nationwide cross-sectional study of 3335 employees was conducted in 320 offices in Japan to estimate the prevalence of building-related symptoms (BRSs) and determine the risk factors related to work environment, Indoor Air Quality, and occupational stress. Data were collected through self-administered questionnaires. The prevalences of general symptoms, eye irritation, and upper respiratory symptoms were 14.4%, 12.1%, and 8.9%, respectively. Multiple logistic regression analyses revealed that eye irritation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 43 publications
5
71
1
Order By: Relevance
“…Recent epidemiological studies have shown strong associations between low RH and the prevalence of DE symptoms, in agreement with controlled studies.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Recent epidemiological studies have shown strong associations between low RH and the prevalence of DE symptoms, in agreement with controlled studies.…”
Section: Resultssupporting
confidence: 83%
“…The prevalence of DE symptoms is between 20% and 40% in offices depending on the recall period; for instance, 1 week, 4 weeks, and 3 months for aircraft . The shorter the recall period the lower is the prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation is that we did not study job stressors and psychological work environment. These factors are found to be associated with SBS in previous studies (Azuma et al, 2014;Bakke et al, 2007;Marmot et al, 2006;Runeson et al, 2006). However, it is less likely that these factors would be related to clinical parameters such as SPT or FeNO.…”
Section: Discussionmentioning
confidence: 78%
“…Female gender (Brasche et al, 2001;Stenberg and Wall, 1995), allergy (Björnsson et al, 1998;Sahlberg et al, 2012), personality traits (Runeson et al, 2004) and lower sense of coherence (Runeson et al, 2003) were reported to be associated with SBS. Moreover, unbalanced psychosocial work environment (Marmot et al, 2006;Runeson et al, 2006) and occupational stress (Azuma et al, 2014;Bakke et al, 2007) have been shown to be related to SBS symptoms. Indoor environmental factors associated with SBS include room temperature (Bakke et al, 2008), relative air humidity (Wolkoff, 2008), building dampness (Mendell et al, 2011;Park et al, 2008), ventilation flow (Seppänen and Fisk, 2004;Sundell et al, 2011), microbial exposure such as molds and bacteria (WHO, 2009), microbial volatile organic compounds (MVOC) (Araki et al, 2010;Sahlberg et al, 2013) and volatile organic compounds (VOC) (Takigawa et al, 2012).…”
mentioning
confidence: 99%
“…Up to now, the psychological impact on office workers' well-being is poorly studied and questioned. Indeed, it has been hypothesized that psychosocial work environment is associated with building symptoms (Azuma et al, 2014;Marmot et al, 2006). The psychosocial parameters should be examined when risk factors of health and comfort are investigated.…”
Section: Importance Of Psychosocial and Personal Factorsmentioning
confidence: 99%